El Control Interno y su incidencia en la gestión administrativa de la empresa de insumos agrícolas orgánicos “comintegra S. A”,cantón Ibarra, año 2012. - Tubay Vergara, Jessenia Alexandra (2012)
The present investigation: "The Internal Control and its impact on the administrative management of the company's organic farm inputs" COMINTEGRA SA "Canton Ibarra in 2012, was created with the purpose of establishing excellent control of the operations performed in the company to see if they are the most effective and efficient for your business progress by allowing know the needs and problems being experienced by the company in order to propose the respective changes to divert it efficiently, effectively and help the entity achieves all its objectives and proposed goals and avoid dangers and surprises along the way. This thesis has been developed according to the guidelines of the exploratory and descriptive bibliographic research, having conducted the study on the current situation of the company have carried out an Internal Control preliminary program where you can view all procedures continue to obtain all information necessary for the evaluation of internal control, data were obtained through interviews, site visits, among others. Also apply management indicators as a tool to measure the efficiency and effectiveness in order to evaluate the use of resources of the company to see if they are well used, also apply the internal control questionnaire with its five components as established COSO I to check the compliance of laws and consider that procedures apply in the accounting records in the company Comintegra SA Once detected all the mistakes and shortcomings make the conclusions and recommendations of this study.